Análisis del cumplimiento tributarío de una cooperativa de ahorro y crédito ubicada en la ciudad de Guayaquil, durante el primer semestre del ejercicio fiscal del año 2008 - Diaz Rodriguez, Roxana (2009)
The subject “ANALYSIS OF the TRIBUTARY FULFILLMENT OF a COOPERATIVE OF SAVING AND CREDIT LOCATED IN the CITY OF GUAYAQUIL, DURING the FIRST SEMESTER OF the FISCAL YEAR OF YEAR 2008”, consisted, as to his it indicates it name, of making an analysis of the documentation of the Cooperative according to the requirements of the Ecuadorian Norms of Accounting, the Tributary Code, the Law of Internal Tributary Regime, the Regulation for the application of the Law of Internal Tributary Regime, and other agreements and regulations, in order to formulate an opinion on its fulfillment. The rise of information, analyzing the proofs of sale of endorsement by the transactions reflected in the financial statements was realized and verifying the conformity of the taxe´s declarations according to the applicable norm; tables and lists of control were elaborated to show the found observations. As result we elaborated the report of tributary audit with all the formalities of law, based in the models proposed by the Fiscal Administration for the independent audit.